Association of dietary inflammatory index, composite dietary antioxidant index and risk of death among adult cancer survivors: findings from the National Health and Nutrition Examination Survey 2001–2018 - Luo, Zhuanbo; Chen, Shiyu; Chen, Peixu; Xiong, Kunlong; Cao, Chao (Frontiers in Immunology, 2025)
BackgroundThe development and progression of cancer can be impacted by the nutrients and components contained in the diet. This research seeks to explore the relationship between the antioxidant and pro-inflammatory properties of diet and the risk of all-cause mortality among cancer survivors.MethodsAdults aged 20 and above who had been diagnosed with cancer and participated in the National Health and Nutrition Examination Survey (NHANES) from 2001 to 2018 were selected for this study. Their survival status was verified using death certificate information from the National Death Index. The study employed two established measures, the Composite Dietary Antioxidant Index (CDAI) and the Dietary Inflammatory Index (DII), to evaluate the antioxidant and inflammatory properties of participants’ diets. A non-linear association between these two dietary indices and mortality was examined respectively using restricted cubic spline (RCS) regression. To quantify the relationship between the indices and mortality risk, multivariable Cox proportional hazards models were employed, generating hazard ratios and corresponding 95% confidence intervals. Furthermore, the study also explored the connection between the CDAI and DII.ResultsIn this study, a total of 3,507 cancer survivors, representing an estimated 20,016,255 cancer survivors in the US, were included in the baseline analysis. The results showed that patients with lower DII or higher CDAI values had better survival rates. RCS regression revealed that both indicators showed linear relationships with all-cause mortality in the crude and adjusted models. It was consistently noted higher CDAI or lower DII was related to a reduced risk of all-cause mortality in cancer survivors in the Cox regression. Moreover, the subgroup analysis demonstrated that these associations hold true across various subgroups, lending credibility to the overall findings of the study. At last, an inverse correlation was observed between CDAI and DII in the diets of cancer survivors.ConclusionThe research suggests that adopting a diet that low in pro-inflammatory foods and high in antioxidants may lower the all-cause mortality in cancer survivors. However, further prospective cohort studies are necessary to confirm these findings.